Crack Self-healing Behavior of Cementitious Composites Incorporating Various Mineral Admixtures - Ahn, Tae-Ho; Kishi, Toshiharu (Journal of Advanced Concrete Technology, 2010)
This study aims to develop and apply self-healing concrete as a new method for crack control and enhanced service life in concrete structure. This concept is one of the maintenance-free methods which, apart from saving direct costs for maintenance and repair, reduces the indirect costs - a saving generally welcomed by contractors. In this research, the self-healing phenomenon of autogenous healing concrete using geo-materials for practical industrial application was investigated. Moreover, a self-healing concrete was fabricated by ready-mixed car in a ready-mixed concrete factory, then used for the construction of artificial water-retaining structures and actual tunnel structures. The results show that the crack of concrete was significantly self-healed up to 28 days re-curing. Crack-width of 0.15mm was self-healed after re-curing for 3 days and the crack width decreased from 0.22 mm to 0.16 mm after re-curing for 7 days. Furthermore, it was almost completely self-healed at 33 days. It was founded that this phenomenon occurred mainly due to the swelling effect, expansion effect and re-crystallization. From these results, it is considered that the utilization of appropriate dosages of geo-materials has a high potential for one of new repairing methods of cracked concrete under the water leakage of underground civil infrastructure such as tunnels.